56‐3: On‐Cell Plus: A New Touch Display Module - Chen, Yu-Tung; Hsu, Ching-Wei; Chen, Neal (SID International Symposium Digest of technical papers, 2024)
"On‐Cell Plus", is designed by setting the same size of active area (AA) of the touch sensor and display, and then uses random mesh pattern to prevent moiré issues. Accordingly, the touch sensor and display cell can be designed and produced independently and demonstrate better touch sensitivity.